Towards the Development of a Framework for Encouraging the Learning of SPICE Model by Using Knowledge Graphs - Fernández Del Carpio, Alvaro (2015)
Software process learning is a relevant aspect on software process improvement. In this paper, we present a framework based on knowledge graphs, in order to evaluate the expertise on ISO 15504 software model (SPICE). Having identified some papers related to the target of the research, we have proposed a framework with modules related to mechanisms, to extract both: information from IT workers and SPI models, for generating the corresponding knowledge graphs and matching them, to determine strengths and weaknesses in the learning process of the SPICE model.